THE ANONYMOUS TEACHERS’ FACTORS OF ASSESSING PARAGRAPH WRITING - Endah Yulia Rahayu (Journal of English for Academic and Specific Purposes, 2020)
Scoring writing is very subjective and mainly relies on a lot on teachers as raters. They play a significant role to meticulously carry out writing evaluations to adjudicate the linguistic and rhetorical features of their students' written responses. Based on the previous studies, the teachers’ factors of knowledge of basic writing assessment, efficacy in selecting assessment method, efficacy in scoring accuracy, and perception in practicing writing assessment can contribute a lot to the quality in teachers’ writing assessment. The  56 junior high school English teachers having at least five years of teaching experience, was invited to fill out the questionnaire and scoring paragraph writing. The results were examined with Multiple Linear Regression analysis. Amongst these factors, only the efficacy in scoring writing accuracy predicts the teachers’ scoring paragraph writing.